PERJANJIAN ABITRASE SEBAGAI PILIHAN PENYELESAIAN SENGKETA PERDATA (Perspektif Undang-undang Nomor 30 Tahun 1999) - Yulianis, M. Sifa Fauzi; Qudussalam, Abdul; Haniyah, Haniyah; Samuji, Samuji; Sodikin, Ali (JURNAL LEGISIA, 2024)
The borderless business world with all the problems that arise requires an effective and efficient problem solving system without many obstacles, one way to resolve business disputes through arbitration, as there is in the agreement of the parties to business people where the agreement in question cannot stand alone without the main agreement, how to resolve disputes arising from the arbitration law review agreement on arbitration agreements. This research is a normative research with an approach based on Law No: 30 of 1999 concerning arbitration and dispute resolution, the arbitration agreement is the main agreement that can still stand alone perfectly. Conversely, in the absence of a principal agreement, the parties may not be able to enter into a binding arbitration agreement.